2014
DOI: 10.1063/1.4864438
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of sensor design for Barkhausen noise measurement using finite element analysis

Abstract: The effects of design parameters for optimizing the performance of sensors for magneticBarkhausen emission measurement are presented. This study was performed using finite element analysis. The design parameters investigated include core material, core-tip curvature, core length, and pole spacing. Considering a combination of permeability and saturation magnetization, iron was selected as the core material among other materials investigated. Although a flat core-tip would result in higher magnetic flux concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…The lower saturation magnetization of the ferrite core may be one reason for the differences in the observed pickup signal with different magnetizing yokes seen in the studies of Vértesy et al [25]. Prabhu Gaunkar et al [14] verified, by means of modelling, that the magnetic flux densities vary with different core materials. They [14] noticed that, among the materials that they studied, the 78 Permalloy had the highest and the iron core had the second highest magnetic flux density values.…”
Section: Materials and Geometry: Magnetization Unitmentioning
confidence: 93%
See 4 more Smart Citations
“…The lower saturation magnetization of the ferrite core may be one reason for the differences in the observed pickup signal with different magnetizing yokes seen in the studies of Vértesy et al [25]. Prabhu Gaunkar et al [14] verified, by means of modelling, that the magnetic flux densities vary with different core materials. They [14] noticed that, among the materials that they studied, the 78 Permalloy had the highest and the iron core had the second highest magnetic flux density values.…”
Section: Materials and Geometry: Magnetization Unitmentioning
confidence: 93%
“…In the U-shape yoke, the copper coil can be wrapped in the upper area of the core. Prabhu Gaunkar et al [14] studied the effect of core length on the magnetic field and concluded, based on their modelling, that the magnetic field strength decreases with increasing core length (path length from pickup to coil). Thus, in the magnetization unit, the copper coil for magnetizing has also been wrapped around both legs as demonstrated in Fig.…”
Section: Materials and Geometry: Magnetization Unitmentioning
confidence: 99%
See 3 more Smart Citations